Determinants affecting entrepreneurial intention among university students / Aina Natasha Bachok - Bachok, Aina Natasha (Faculty of Business and Management, 2020)
The purpose of the study is to investigate the determinants affecting entrepreneurial intention among university student. This study comprises three independent variables which are personality trait, current economic environment and knowledge and environment. This study focuses on university students in Universiti Teknologi MARA (UiTM) Melaka (City Campus). 200 questionnaires were distributed to the respondent in UITM Melaka. However, only 170 completed questionnaires were received and recorded. This research analyses the result by using Statistics Packages for Social Sciences (SPSS) software version 24. The result recorded personality trait and current economic environment have a significant relationship on the entrepreneurial intentions among university student.